2016
DOI: 10.1200/jco.2016.68.1106
|View full text |Cite
|
Sign up to set email alerts
|

Safety, Antitumor Activity, and Immune Activation of Pegylated Recombinant Human Interleukin-10 (AM0010) in Patients With Advanced Solid Tumors

Abstract: Interleukin-10 (IL-10) stimulates the expansion and cytotoxicity of tumor-infiltrating CD8+ T cells and inhibits inflammatory CD4+ T cells. Pegylation prolongs the serum concentration of IL-10 without changing the immunologic profile. This phase I study sought to determine the safety and antitumor activity of AM0010. Patients and MethodsPatients with selected advanced solid tumors were treated with AM0010 in a dose-escalation study, which was followed by a renal cell cancer (RCC) dose-expansion cohort. AM0010 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
150
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 188 publications
(157 citation statements)
references
References 26 publications
6
150
1
Order By: Relevance
“…Similarly, immune checkpoint blockade therapy using antibodies directed against immunomodulatory receptors and ligands induces long-term survival in a considerable portion of CM patients [73] but shows only limited activity in metastatic UM patients with extended responses in some patients [7483]. A recent phase I trial with AM0010, a pegylated recombinant IL-10, showed responses of solid tumors with BRCA1-associated protein 1 (BAP1) mutations, among which is a UM [84]. …”
Section: Clinical Features Of Uveal Melanomamentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, immune checkpoint blockade therapy using antibodies directed against immunomodulatory receptors and ligands induces long-term survival in a considerable portion of CM patients [73] but shows only limited activity in metastatic UM patients with extended responses in some patients [7483]. A recent phase I trial with AM0010, a pegylated recombinant IL-10, showed responses of solid tumors with BRCA1-associated protein 1 (BAP1) mutations, among which is a UM [84]. …”
Section: Clinical Features Of Uveal Melanomamentioning
confidence: 99%
“…Gene expression data from 79 cases of primary UM from the TCGA cohort were used for the identification of genes that are differentially expressed in cases that yielded distant metastases later on as compared to cases without progression to metastatic disease. Statistically significant gene expression differences were obtained by analysis using the bootstrapping algorithm significance analysis of microarrays as described [84]. Expression values over the mean value are indicated in red , values below the mean in blue , and values at the mean in white ; the intensity of the color corresponds to the distances from the mean as indicated in the red-blue bar on top of the diagram .…”
Section: Genetics Of Uveal Melanomamentioning
confidence: 99%
See 1 more Smart Citation
“…In this expansion cohort, patients were treated with daily AM0010 in the dose‐escalation and illustrated the drug is well tolerated. Also, the authors observed drug‐related grade 3 and 4 adverse events) in 15% of patients (NCT02009449) (Naing et al, 2016). More recently, a Phase 1b clinical trial was reported on the antitumor activity of AM0010 in combination with nivolumab or pembrolizumab in RCC patients ( n = 38).…”
Section: Combination Therapy Of Cytokines and Pd‐1/pd‐l1 Inhibitorsmentioning
confidence: 99%
“…TNFα has high systemic toxicity, but can be administered to isolated limbs containing melanoma or sarcoma with reasonable safety and high rates of complete response [Lienard et al, ]. Systemic versions of IL‐15, IL‐18, and IL‐10 have all met with acceptable safety profiles in phase I trials, although it is not clear yet that they will be effective at tumor control in humans [Robertson et al, ; Conlon et al, ; Naing et al, ; Rosario et al, ]. Overall, systemic administration of defined cytokines is associated with significant side effects caused by overwhelming immune activation.…”
Section: Agents That Benefit From Local Deliverymentioning
confidence: 99%